A formação de comunidades virtuais no portal Comunique-se: um primeiro olhar - Escobar, Juliana Lúcia (2006)
This paper investigates the website “Comunique-se” in order to verify whether it favors the formation of virtual communities. As a result of this investigation, we concluded that the website offers the technical prerequisites that allow the creation of virtual communities, since it engenders “virtual settlements” (symbolically delimited places in cyberspace) wherein one may observe the practice of mutual interaction, allowing for an extended duration (permanence) of the relationship between interacting agents. Notes on the classic concept of community according to authors such as Max Weber, Ferdinand Tönnies, Emile Durkheim and Martin Buber, as well as its current reconfigurations in the context of virtual communities. We seek to elaborate a minimal definition that includes some requisites regarding the formation of virtual communities in cyberspace.